ANALYSIS EFFECTIVENESS OF DISTRIBUTION AND FORECASTING IN KLUG ENVELOPE COMPANY IN SURABAYA - Eduard Arnando; Yoshua Nathaniel (AIBPM Publisher, 2018)
The purpose of this study aims to analyzethe effectiveness of distribution and forecasting on the company envelope Klug in Surabaya, As for the background of this writing because in the company we choose not yet use forecasting to predict how much the future sales, and distribution channels in use in this company which only entrusts the goods to a particular store. The function of the forecast will be known when making decisions. A good decision is a decision based on consideration of what will happen when the decision is made. Distribution is one aspect of marketing. Distribution can also be interpreted as a marketing activity that seeks to smoothen and facilitate the delivery of goods and services from producers to consumers. If forecast is done we can predict how far distribution can be done. The outcome of this research is the forecast and distribution in this company klug envelopes are interrelated if forecast done properly then it can be decided the right distribution channels so that the sale of the envelope itself. Keywords: Distribution, Klug Envelope, Forecasting ,Effectiveness ,Sales